Design Of Low Cost, Easy To Use And Portable Vision Test Tool For Rural Populations - Ming, Yee Zen (Universiti Teknologi PETRONAS, 2014)
This report describes the design and implementation of a vision screening system dedicated for android based devices. It is used as a vision test tool for the rural population especially the senior citizens. The senior citizens in the rural areas do not have the means to regularly visit clinics or hospital to undergo eye check-up as it is inconvenient for them to travel far. Hence, this project is aimed to design a user-friendly eye test application that comes with multi-lingual language option. With this application, the senior citizens can run the eye test at the comfort of their home. The designed application is portable and simple for the user to run without any prior experiences. It comes with the visual acuity eye test. Input from the user will be analysed and the eye score will be displayed at the end of the test with an appropriate recommendation to the user. Experiments have been conducted on 15 university students. Those with vision problems are taken as samples to measure the sensitivity of the application. The results obtained show that the application has constantly achieved more than 80% of accuracy in terms of specificity and sensitivity.